Biological Reclamation Using a Sewage Sludge-Based Substrate – A Way to Ensure Sustainable Development of Urban Areas - Ivan Tymchuk (Polish Society of Ecological Engineering (PTIE), 2022)
Monitoring studies were carried out on the territory of the Lviv wastewater treatment plants. The volumes of accumulated stocks of the sludge site were determined, its qualitative and quantitative indicators were identified, and the presence of limiting factors was established. Based on the obtained data, 2-D models characterizing the vertical and horizontal accumulation of elements were created. Bioindication studies were conducted to determine the feasibility of using sewage sludge as a growth substrate. Modeling was performed to determine the potential area of reclaimed land